Cigarette Use, Lung Cancer Screening Eligibility and Completion Among Persons With Poor Mental Health - Monica Hernandez; Anastasia Rogova; Lorraine R. Reitzel; Lisa M. Lowenstein; Robert J. Volk (Cancer Medicine)
ABSTRACT Background Depression and mental distress are associated with greater cigarette use; however, it remains unclear how poor mental health relates to eligibility and completion of lung cancer screening (LCS). Methods Study of a 2022 Behavioral Risk Factor Surveillance System (BRFSS) sample of adults aged 50+. Key mental health exposures for this paper were (i) any history of a depressive disorder, and (ii) frequent mental distress (FMD) in the last month. Descriptive analyses were conducted on all variables and ran separately on each mental health exposure to explore associations between mental health conditions, cigarette use, LCS eligibility, and completion. Results Compared to adults without a depressive history, adults with a depressive history were more likely to currently smoke (19.9% vs. 10.8%); have a slightly higher average pack‐year history (26.8 vs. 24.0 years); and were more likely to be eligible for LCS (18.9% vs. 10.8%). Among adults eligible for LCS, there was no difference in completion of screening in the last year between adults with versus without a depressive history (19.4% vs. 18.7%). A similar pattern of findings was observed for people with and without FMD. Conclusions Cigarette use is more common among persons with a history of depression or FMD, yet they are screened for lung cancer at similar rates compared to their counterparts without a history of depression or FMD. LCS rates are also low among persons with poor mental health, mirroring screening among general U.S. adults. Mechanisms to increase LCS rates among adults with mental health conditions are discussed.